Process mapping for BPR at Torbay hospital - Wickes, Martin J. (Cranfield University, 2001)
This report documents a process mapping exercise conducted at Torbay Hospital and subsequent process improvement exercise, forming the initial stage of a Business Process Re-engineering programme. The report reviews pertinent research, concluding that whilst BPR exercises continue to be a popular method of facilitating efficiency gains, few hospitals seem to report the success of their programme or methodologies. As such, every hospital starts the programme from square one. The report therefore documents the methodology employed for data collection, as well as the options for representing the data, once collected; IDEF 3 is recommended as the most appropriate means. The thesis then discusses the tactics involved in running a BPR exercise in the Endoscopy Unit of Torbay Hospital and details subsequent recommendations for improvement.